Randomized Controlled Study Comparing Use of Propofol Plus Fentanyl versus Midazolam Plus Fentanyl as Sedation in Diagnostic Endoscopy in Patients with Advanced Liver Disease. (26th September 2017) - Ahmed, Sameh Abdelkhalik; Selim, Amal; Hawash, Nehad; Tawfik, Ahmed Khaled; Yousef, Mohamed; Kobtan, Abdelrahman; Badawi, Rehab; Elnawasany, Sally; Elkhouly, Reham Abdelkader; Hanafy, Amr Shaaban; Rizk, Fatma H.; Mansour, Loai; et al.
Abstract : Objectives. We aimed to investigate the safety and efficacy of propofol plus fentanyl versus midazolam plus fentanyl as sedative for patients with advanced liver disease presented for gastrointestinal endoscopy. Methods. A total of 100 patients with liver cirrhosis referred for upper endoscopy were enrolled and divided equally in two groups, midazolam plus fentanyl group and propofol plus fentanyl group. All patients were subjected to history taking, estimation of level of sedation, endoscopist rating, and hemodynamic parameters including oxygen saturation, heart rate, mean arterial pressure, incidence of side effect as (bradycardia, hypotension, hypoxia, nausea and vomiting, cough, shivering, or diplopia), time needed for complete recovery, and time needed for discharge. Results. There was no statistical significant difference between the studied groups regarding age, sex, weight, Child–Pugh classification score, type and duration of endoscopic intervention, time needed for complete recovery, or time needed for discharge. Complication rates were similar in both groups except for mean arterial blood pressure which was significantly lower in group of patients receiving propofol and fentanyl (P = 0.001 ). Conclusion. The use of either propofol or midazolam in combination to fentanyl is effective in sedation of patients with advanced liver diseases presented for upper GIT endoscope. The trial is registered with ClinicalTrials.gov Identifier:NCT03063866 .